Pengaruh Penambahan Abu Kayu, Kapur Dan Styrofoam Sebagai Bahan Campuran Pada Tanah Lempung Terhadap Nilai CBR: The Effect Of Adding Wood Ash, Lime And Styrofoam As Mixed Materials In Clay On CBR Value - Febri Nuryadi Wicaksono; Fatma Sarie; Okrobianus Hendri (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Building construction is influenced by the existing soil conditions. Clay soil is one of the soils that have deficiencies, both in bearing strength and the nature of the soil itself, so soil stabilization is needed. Soil stabilization is an attempt to improve soil properties. The purpose of this study was to analyze the physical and mechanical properties of the soil and to analyze the effect of wood ash, lime, and styrofoam on the CBR value. The soil samples were located in Tumbang Liting Village, Kasongan Lama Village, Katingan Regency, Central Kalimantan. To overcome this unstable soil, alternative materials were added in this study, the materials used were wood ash, lime, and styrofoam. The mixture of materials mentioned for stabilization is expected to improve soil properties. For the percentage of mixed variations, namely 5%, 7.5%, and 10%. Soil testing is carried out according to ASTM (American Society for Testing and Materials) standards. The results obtained from the test show that the CBR value of clay occurs in each variation of the mixture. For the percentage of the original soil, the CBR value was obtained by 3.05%. Soil yields with a mixture of wood ash, lime, and styrofoam with the highest CBR percentage values ​​occurred at variations of 5%, 7.5%, and 10% increased during the 7-day ripening period of 5.45%; 6.40%; 7.39%. For the highest design CBR value, there was a mixture of soil, wood ash, kapu, and styrofoam 10% 7-day curing of 7.39%, an increase of 142.30% from the original soil CBR, so that the mixture of native soil, wood ash, lime, and styrofoam had an effect on soil stabilization.